Prognostic value of radiologic extranodal extension in patients with hypopharyngeal cancer treated with primary chemoradiation. (March 2021) - Fan, Kang-Hsing; Yeh, Chih-Hua; Hung, Sheng-Ping; Kang, Chung-Jan; Huang, Shiang-Fu; Chang, Kai-Ping; Wang, Hung-Ming; Chia-Hsun Hsieh, Jason; Lin, Chien-Yu; Cheng, Ann-Joy; Ng, Shu-Hang; Tung-Chieh Chang, Joseph
Highlights: Radiologic extranodal extension (rENE) correlated with poor treatment outcomes. rENE correlated with clinical N stage in patients with hypopharyngeal cancer. Metastatic lymph nodes >6 cm coexisted with rENE and correlated with poor survival. It may be more appropriate to classify as N3b disease in future staging systems. rENE of lymph nodes <6 cm should be staged as N3a disease. Abstract: Background and purpose: We aimed to evaluate the prognostic value of radiologic extranodal extension (rENE) in patients with hypopharyngeal cancer (HPC) treated with primary chemoradiation. Materials and methods: Cancer registry data were reviewed from 2005 to 2014. Inclusion criteria included HPC, clinical N1–3 disease (AJCC staging system, 7th edition), and receiving radiotherapy. Patients with M1 diseaseor with synchronous/metachronous cancer were excluded. Staging images were reviewed by two radiologists. rENE was defined as infiltration of adjacent fat/muscles, irregular nodal surface, or irregular capsular enhancement. Clinical stage, rENE status, and clinical outcome were analyzed. Results: Overall, 355 patients were included. Patients with rENE had lower 3-year overall survival (OS) and recurrence-free survival (RFS) rates. Univariate analysis showed that clinical T4 or N3 stage, overall stage IV, and rENE correlated with OS and RFS. In multivariate analysis, clinical T4 or N3 stage correlated with poor OS, while clinical T4 or N3 stage and rENE were independent predictors of poor RFS. N1/2 without rENE was designated as Group 1, N1/2 with rENE as Group 2, and N3 with/without rENE as Group 3. The 3-year RFS rates in Groups 1, 2, and 3 were 55.8%, 41.0%, and 29.3%, respectively. The 3-year RFS rate in Group 1 was significantly higher than that in the other two groups. Conclusions: rENE is an adverse prognostic factor for survival in patients with HPC treated with primary chemoradiation. It correlated with inferior RFS regardless of N stage. rENE may be used as a criterion for clinical ENE in future staging systems.